2009
DOI: 10.1021/bi900357j
|View full text |Cite
|
Sign up to set email alerts
|

Probing Anomalous Structural Features in Polypurine Tract-Containing RNA−DNA Hybrids with Neomycin B

Abstract: During (−)-strand DNA synthesis in retroviruses and Saccharomyces cerevisiae LTR retrotransposons, a purine rich region of the RNA template, known as the polypurine tract (PPT), is resistant to RNase H-mediated hydrolysis and subsequently serves as a primer for (+)-strand, DNAdependent DNA synthesis. Although HIV-1 and Ty3 PPT sequences share no sequence similarity beyond the fact that both include runs of purine ribonucleotides, it has been suggested that these PPTs are processed by their cognate reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In our hands, this platform enabled the investigation of intact duplexes formed by the 20-mer DNA/RNA oligonucleotides that mimicked the HIV-1 polypurine tract, 22,30 or by the 6-base-pair kissing interaction of the dimerization initiation site domain of the HIV-1 genome. 31,32 This approach was employed here to assess the formation of the minimal kissing complexes involving much fewer intermolecular pairing interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our hands, this platform enabled the investigation of intact duplexes formed by the 20-mer DNA/RNA oligonucleotides that mimicked the HIV-1 polypurine tract, 22,30 or by the 6-base-pair kissing interaction of the dimerization initiation site domain of the HIV-1 genome. 31,32 This approach was employed here to assess the formation of the minimal kissing complexes involving much fewer intermolecular pairing interactions.…”
Section: Resultsmentioning
confidence: 99%
“…18 It is well-established that, under proper conditions, ESI-MS is capable of taking accurate snapshots of binding equilibria without perturbation of the equilibrium positions in solution. 19,20 This favorable feature allows not only to monitor multiple simultaneous equilibria in solution, 21,22 but also to determine the partitioning between free and bound species at equilibrium, which are comparable to dissociation constants obtained by traditional methods. 23,24 Optical tweezers-based single-molecule force spectroscopy can be used to measure RNA unfolding/refolding kinetics, 8,25 and to observe specific behaviors of individual molecules, which may be masked by the ensemble averaging in bulk techniques.…”
Section: Introductionmentioning
confidence: 90%
“…Consistent with these observations, 1 H-NMR of a 1:1 neomycin B:PPT hybrid showed shifts in imino proton signals at positions corresponding to the PPT/ U3 junction and evidence for a second binding site as the ratio was increased. Subsequent NMR analysis in the presence of HIV-1 RT indicated contact between protein and nucleic acid in the same two regions, while equivalent findings with RT from the LTR-retrotransposon Ty3 and its cognate PPT (Brinson et al 2009) suggested that structural features at either extremity of the PPT may be a more general feature contributing to its recognition. Such data are not intended to imply the therapeutic use of neomycin B, which is known to bind to a variety of RNA structures, but rather to illustrate that more selective nucleic acid ligands could be developed to disrupt (+) strand DNA synthesis.…”
Section: Protein Synthesis and Ribosomal Frameshifting: A Delicate Bamentioning
confidence: 86%
“…A purine tract found in the HIV-1 sequence[55] and trinucleotide repeat (TNR) sequences[56] impact polymerase elongation. It was also shown that repeat sequence of (CG) 14 induces large deletions in transcripts in mammalian cells [57].…”
Section: Discussionmentioning
confidence: 99%